A review on cylindrospermopsin: The global occurrence, detection, toxicity and degradation of a potent cyanotoxin - De La Cruz, Armah A.; Hiskia, Anastasia; Kaloudis, Triantafyllos; Chernoff, Neil; Hill, Donna; Antoniou, Maria G.; He, Xuexiang; Loftin, Keith; O'Shea, Kevin; Zhao, Cen; Pelaez, Miguel; Han, Changseok; et al. (My University, 2013)
Cylindrospermopsin is an important cyanobacterial toxin found in water bodies worldwide. The ever-increasing and global occurrence of massive and prolonged blooms of cylindrospermopsin-producing cyanobacteria poses a potential threat to both human and ecosystem health. Its toxicity is associated with metabolic activation and may involve mechanisms that adversely affect a wide variety of targets in an organism. Cylindrospermopsin has been shown to be cytotoxic, dermatotoxic, genotoxic, hepatotoxic in vivo, developmentally toxic, and may be carcinogenic. Human exposure may occur through drinking water, during recreational activities and by consuming foods in which the toxin may have bioaccumulated. Drinking water shortages of sufficient quality coupled with growing human pressures and climate variability and change necessitate an integrated and sustainable water management program. This review presents an overview of the importance of cylindrospermopsin, its detection, toxicity, worldwide distribution, and lastly, its chemical and biological degradation and removal by natural processes and drinking water treatment processes. © 2013 The Royal Society of Chemistry.
Keywords: Chemistry; Environmental Sciences